Transparency of electoral accountability in amazonian municipalities - Silva, Gabriele Assunção da (2025)
Purpose: The general objective of the article is to analyze whether the electoral accountability of mayoral candidates during the 2020 Amazonian municipal elections promotes transparency in campaign financing and to compare financing with re-election in the electoral contest. Methodology: The content analysis technique was used to establish the categories and subcategories of transparency present in electoral legislation, and documentary analysis of the financial statements was conducted. Results: Among the analyzed dimensions of transparency, compliance was predominant, followed by disclosure and accountability. However, the analysis of the accountability reports of mayoral candidates in Amazonas revealed significant flaws, such as the absence of mandatory information, especially among the least voted candidates. Regarding campaign financing sources, the Special Fund was the main source of revenue, with the majority of expenses directed towards propaganda and advertising. The analysis of the financial statements of the winning and second-placed candidates revealed disparities in the completeness of information, particularly among re-elected candidates. Contributions of the Study: In the academic context, this article seeks to strengthen the literature on the subject and contribute to the development of research that can assist in understanding electoral accountability and its relationships with transparency and social control. Additionally, the social contribution of the research lies in providing insights for society to understand and monitor the use of public resources in these political activities.